Using Sleman’s Verbal Autopsy Health and Demographic Surveillance Data to Distinguish Ways of Death - Beta Ahlam Gizela; Idha Arfianti Wiraagni; Suhartini; Nurholis Majid Public (Indian Journal of Forensic Medicine & Toxicology, 2021)
Death can occur anywhere, with or without prior treatment by a healthcare professional. A good and complete death registry will meet the information needs. Such a registry will also enhance community safety efforts and policymaking in the health and population sectors. Analysis of risk factors, signs, and symptoms observed before death provides useful information for estimating diseases or causes of death. Verbal autopsy data must be explored in more depth to protect public law and improve health statistics.Methods: This research used observational design. Data obtained from the Health and Demographic Surveillance System of Sleman. Research subjects were all deaths recorded in verbal autopsy document from 2014-2018. Descriptive statistical analysis was used.Results: Differences in the proportion of gender from 2014-2017 were observed, where the number of women was higher than men. Most deaths were above 65 years of age. Most deaths were natural deaths. Unnatural deaths were caused by traffic accidents, drowning, murder, and others, with the most number of cases occurring in 2014 (12%). Indeterminate deaths occurred annually, with the most cases in 2017 (13%). Conclusions: Verbal autopsy has succeeded in distinguishing between natural and unnatural death.